2018
DOI: 10.1016/j.tranon.2017.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric HCMV/HSV-1 and Δγ134.5 oncolytic herpes simplex virus elicit immune mediated antigliomal effect and antitumor memory

Abstract: Malignant gliomas are the most common primary brain tumor and are characterized by rapid and highly invasive growth. Because of their poor prognosis, new therapeutic strategies are needed. Oncolytic virotherapy (OV) is a promising strategy for treating cancer that incorporates both direct viral replication mediated and immune mediated mechanisms to kill tumor cells. C134 is a next generation Δγ134.5 oHSV-1 with improved intratumoral viral replication. It remains safe in the CNS environment by inducing early IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 29 publications
(47 reference statements)
1
26
0
Order By: Relevance
“…Convincing evidence has revealed that the tumour tissue environment consists of heterogeneous components, such as tumour cells, fibroblasts, and immune cells [4346]. The interactions between these cells define the microenvironment of tumour cells and are involved in the growth and metastasis of tumours [47].…”
Section: Discussionmentioning
confidence: 99%
“…Convincing evidence has revealed that the tumour tissue environment consists of heterogeneous components, such as tumour cells, fibroblasts, and immune cells [4346]. The interactions between these cells define the microenvironment of tumour cells and are involved in the growth and metastasis of tumours [47].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells with relative low passage numbers (<12 passages) were used in the study before returning for a "low" passage form of the cell line to minimize genetic drift in our studies. Viruses have been previously described (22), but in brief; HSV-1 (F) strain and R3616, the Dg 1 34.5 recombinant, were kindly provided by Dr. Bernard Roizman (University of Chicago, Chicago, IL; ref. 23).…”
Section: Cell Lines and Virusesmentioning
confidence: 99%
“…DNA was extracted by DNeasy blood and tissue kit (Qiagen) per the manufacturer's instructions. Virus recovery was measured by Taq-Man quantitative PCR (22). Briefly, extracted DNA samples were incubated with the following HSV-specific primers and probes for HSV polymerase (sequences kindly provided by Dr. Fred Lakeman University of Alabama at Birmingham, Birmingham, Alabama): PolF (forward), 5 0 -ACC GCC GAA CTG AGC AGA C-3 0 ; and PolR (reverse), 5 0 -TGA GCT TGT AAT ACA CCG TCA GGT-3 0 .…”
Section: Viral Replication (In Vivo)mentioning
confidence: 99%
“…Following a different strategy, HSV-1 C134 was developed as a chimeric virus that includes not only the deletion of γ 1 34.5 loci but also the expression of human cytomegalovirus (HCMV) IRS1 gene. This insertion increases viral replication and lytic effect when administered intrathecally in a murine GBM tumor model inducing antitumor T cell mediated immune responses, which elicit long systemic immune-memory enhancing survival [ 32 , 33 ].…”
Section: Dna Viruses Proposed As Glioma Oncolytic Agentsmentioning
confidence: 99%